A mild form of rituximab-associated lung injury in two adolescents treated for nephrotic syndrome. (9th December 2015) - Spatafora, Mario; Bellini, Tommaso; Giordano, Carmela; Ghiggeri, Gian Marco
Abstract : Rituximab is used as a steroid/calcineurin inhibitor-saving agent in patients with nephrotic syndrome. Safety is a crucial issue for justifying widespread use of the drug in this clinical setting. Rituximab-associated lung injury (RALI) is a severe and potentially life-threatening complication in oncohaematological and rheumatological patients, while it has only been anecdotally reported in association with idiopathic nephrotic syndrome (2 cases described, 1 with fatal outcome). We describe a benign form of RALI occurring in two adolescents treated with rituximab (single pulse of 375 mg/m 2 ) for nephrotic syndrome. Before treatment, the patients were in good clinical condition while receiving a combination of steroids and calcineurin inhibitors (tacrolimus, case 1 and cyclosporine, case 2). The two patients developed full blown RALI (ie, ground-glass lesions on CT, negative bronchoscopy with bronchoalveolar lavage and deficit in diffusion lung CO transfer), 14 and 40 days after rituximab infusion, respectively. Recovery was rapid and complete after administering steroids in case 1 and with no therapy in case 2. We conclude that RALI may occur in stable non-immunocompromised patients with nephrotic syndrome and its frequency may be higher than expected. Clinical presentation may be mild and resolve after steroids, suggesting hypersensitivity as the main mechanism. Rapid recognition and prompt steroid therapy, if needed, are mandatory for resolution.